Aktivitas Antihipertensi Fraksi Air Ekstrak Etanol Labu Siam (Sechium edule (Jacq.) Swartz.) pada Tikus Hipertensi yang Diindukasi Monosodium Glutamat - Agatha Ivo Yosehine; Kiki Damayanti; Yance Anas; Achmad Quraisy Aljufri; Dwi Meilani (CENDEKIA EKSAKTA, 2026)
The ethanol extract of chayote has been proven to exhibit antihypertensive activity in monosodium glutamate (MSG)-induced hypertensive rats. Fractionation was conducted to further investigate the active compounds responsible for reducing blood pressure. This study aimed to evaluate the antihypertensive activity of the aqueous fraction of chayote ethanol extract (AFCEE) in MSG-induced hypertensive rats. This experimental study employed a post-test-only control group design. The extract was prepared using the maceration method and the aqueous fraction was obtained through liquid-liquid fractionation. Hypertension in rats was induced by oral administration of MSG at a dose of 100 mg/kg body weight/day for 14 days. The hypertensive rats were then divided into five groups. Group I (negative control) received 0.5% sodium carboxymethyl cellulose (CMC-Na) at a dose of 12.5 mL/kg body weight. Group II (positive control) received furosemide at a dose of 5.04 mg/kg body weight/day. Groups III, IV, and V received AFCEE at doses of 33, 66, and 132 mg/kg body weight, respectively, for 14 days. The reductions in systolic and diastolic blood pressure following AFCEE administration were analyzed using the Mann–Whitney test at a 95% confidence level. AFCEE was found to reduce both systolic and diastolic blood pressure in hypertensive rats. Therefore, AFCEE exhibits antihypertensive activity.